The impact of age on survival and excess mortality after autologous hematopoietic cell transplantation in newly diagnosed multiple myeloma patients - Shohei Mizuno; Luuk Gras; Laurien G.A. Baaij; Linda Koster; Anita D'Souza; Parameswaran N. Hari; Noel Estrada-Merly; Wael Saber; Andrew J. Cowan; Minako Iida; Shinichiro Okamoto; Hiroyuki Takamatsu; et al. (Haematologica)
Despite the availability of novel agents, autologous hematopoietic cell transplantation (auto-HCT) remains the standard of care in newly diagnosed multiple myeloma (MM) patients. The impact of age on overall survival (OS), progression-free survival (PFS), relapse incidence, non-relapse mortality (NRM), and excess mortality (taking account of general population mortality) was investigated using information on 61,797 MM patients transplanted between 2013 and 2017. The median age at auto-HCT was 60.8 (range: 18.1–83.2) years of whom 2.0% were 18–39 years, 68.9% 40–64 years, 21.8% 65–69 years, 6.5% 70–74 years, and 0.8% ≥75 years of age, respectively. The corresponding OS probabilities at three years were 85.9%, 82.8%, 81.1%, 78.4%, and 74.8%, respectively (p<0.001). Excess mortality cumulative incidences were 13.1%, 15.0%, 14.6%, 15.0%, and 14.1% at three years, respectively (p=0.67). In multivariable analyses, older age was a significant risk factor for OS, PFS, and NRM but not for excess mortality or relapse risk. Our results indicate that advanced age alone should not preclude the use of auto-HCT in patients with MM.